An Analysis of Classroom Management and Manner Used by English Teacher at Seventh Grade of MTsN 3 Lima Puluh Kota - Siti Nurliza; Loli Safitri; Eliza Eliza; Hilma Pami Putri (Pusdikra-Publishing.com, 2024)
Classroom management is multifaceted and is the concept of everything in the classroom. Classroom management is an action used by teachers to create an effective and good cooperation in interaction. Classroom management is also defined as the teacher's effort to form an effective environment for learning and teaching, while manner is the teacher ways treat their students in class.. This study focuses on classroom management and manner used by English teachers in seventh grade MTsN 3 Lima Puluh Kota. Therefore, this study is intended describe classroom management and manner used by teachers in teaching English. The researchers using descriptive qualitative with observation and interview as the instrument. Researchers examined two teachers who taught English in the seventh grade of MTsN 3 Lima Puluh Kota. Researchers describe the process of teachers managing classes and the manner of teachers in teaching. Researchers concluded that classroom management and teacher manner are quite good and use existing components in classroom management and manner, although there are some components that are not always implemented by teachers every time they teach in class.